Propagação in vitro e ex vitro, aspectos anatômicos e fisiológicos de Neoregelia concentrica (Bromeliaceae) - Martins, João Paulo Rodrigues (2012)
The spread in vitro may contribute to the multiplication of several species of commercial interest, as bromeliads. However, in vitro culture conditions can induce the formation of plants with poorly developed structures and tissues that can harm the subsequent ex vitro establishment. Thus, the objective was to develop a protocol for the propagation of bromeliad Neoregelia concentrica, taking into account anatomical and physiological aspects. The first experiment concerning the multiplication, was conducted from plants of N. concentrica previously established in vitro and with 180 days old. These were inoculated into test tubes containing MS medium supplemented with 6-benzylaminopurine (BAP) or kinetin (KIN) at 0.0; 5.0; 10.0 and 15.0 µM. At 60 days were analyzed for agronomic parameters and random collection of three plants of each treatment for morphoanatomical analysis. The second experiment, referring to the rooting, was carried out by two methods, in vitro and ex vitro. In vitro rooting, shoots multiplied with 15.0 µM of BAP were cultured for 60 days on MS medium supplemented with indole-3-butyric acid (IBA) or naphthalene-acetic acid (NAA) at 0.0; 1.0;, 2.0; 3.0 and 4.0 µM. For ex vitro rooting, shoots multiplied with 15.0 µM of BAP had their bases immersed for 60 minutes in a solution of IBA or NAA at 0.0; 5.0; 10.0 and 15.0 µM. After immersion, the shoots were planted in plastic trays containing vermiculite and grown for 45 days. At the end of each method of rooting analysis was performed character phytotechnical. In the third experiment, referring to the acclimatization, plants N. concentrica multiplicated and rooted in vitro with 15.0 µM of BAP and NAA 3.0 µM, respectively, were planted in plastic trays containing vermiculite and grown under light levels 30%, 50%, 70% and 100% for 28 days. The analysis of fluorescence was performed every 7 days and the evaluation of characters phytotechnical at 28 days of acclimatization. In vitro multiplication, it was found that increased levels of cytokines induced higher emission x of shoots, and the formation of leaf tissues thicker, the use of BAP and more efficient with regard to the KIN. In the second experiment, we observed a higher rooting in vitro (30 days) and greater number of roots in shoots grown in medium containing 3.0 µM NAA, already in ex vitro rooting, we observed a higher number of roots and with greater length mean when applied 5.0 µM IBA. In the acclimatization, it was found less stress in plants grown under partial reduction of light level, highlighting the level of 50% due to recovery in less time and greater growth of N. concentrica. It was possible to establish an efficient protocol for the propagation of bromeliads N. concentrica.